Intra-vehicular communication protocol for iot enabled vehicle health monitoring system: challenges, issues, and solutions - Karim, Mahima; Rahman, Md. Arafatur; Tan,, Sze Wei; Atiquzzaman,, Mohammed; Pillai,, Prashant; Ali H., Alenezi (IEEE, 2024)
IoT is a groundbreaking technology that enables wireless interoperability between devices without human intervention. It has become an integral part of human life and has made significant advancements in the automotive industry. The combination of vehicular networks and IoT has opened up new possibilities but has also led to challenges such as degraded QoS (Quality of Service), network congestion, packet loss, transmission delay, intrusions, etc. These problems are also apparent in vehicular health monitoring systems. To overcome such challenges, it is necessary to develop an intricate framework that can address them all. TCP/IP is a five-layer-based standardized communication protocol that facilitates communication between devices over the internet. Unique network protocols and functions are authorized to each of the five layers. In this paper, a comprehensive survey is done on all the recent studies on the five communication layer protocols, their functionalities, and practical challenges associated with each of them for an intra- vehicular health monitoring system (IVHMS). Analyzing them, a novel taxonomy is also proposed with visual representation. In the end, this paper proposes a cross-layer-based framework to address communication- related complexities. This cross-layer model aims to integrate all the dynamic capabilities of the five protocol layers (Application, Transport, Network, Data Link & Physical) and resolve issues within each layer by implementing functionalities of other layer protocols. Future research scopes and possibilities of the proposed system are also discussed.